TRADISI UPACARA ATIB KO AMBAI KECAMATAN KUBU KABUPATEN ROKAN HILIR - Emi Karlina Karlina; Isjoni '; Kamaruddin ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: The tradition of every society is realized in various forms one of which is to perform the traditional ceremony which aims to get closer and redeploy attachment between society as a whole which in the implementation of the tradition itself there are symbols and terms of a bona fide religious significance for society implement and believe the purpose and function of the tradition. The ceremony Atib Ko Ambai a community tradition in maintaining Kubu village or a ceremony mendo'a for the purpose of begging salvation or reject all of reinforcements that will befall the community with infectious diseases such as diarrhea, measles and other diseases. Uniquely Ko Ambai ceremony Atib is only performed by men only and do 1 (one) time in one year exactly on day 3 (three) months of Shawwal. The exercise was followed by the whole of society both local residents and visitors. The purpose of this study was to determine the history of the tradition of the ceremony Atib Ko Ambai in District Kubu Rokan Hilir, to determine the factors that encourage people to do traditional ceremony Kubu Atib Ko Ambai Kubu Sub Rokan Hilir, to know the process of implementation of the tradition ceremony Atib Ko Ambai Sub Kubu Rokan Hilir, and to determine the function of tradition ceremony Atib Ko Ambai for society Kubu Kubu Sub Rokan Hilir. The method used in this study is the historical method and qualitative methods. Data were obtained from interviews and analyzed in its own language. The research location is in the district of Kubu Rokan Hilir. When the study started from the seminar proposal to the Thesis exam. Data collection techniques used are observation, interview techniques, technical documentation and technical literature. Results from this study are the factors that encourage people to camp in implementing ceremony Atib Ko Ambai tradition every year that there are two factors. The first factor is the internal factor is afactor that comes from a person or individual, then the second factor is external factors which are factors that come from outside oneself. Keywords: Tradition, Ceremony, Atib Ko Ambai